Pengaruh Jumlah Uang Beredar (JUB), BI Rate dan Inflasi Terhadap Pertumbuhan Ekonomi di Indonesia Periode 2009-2018 - Annisa Dewi Ambarwati; I Made Sara; Ita Sylvia Azita Aziz (Warmadewa Economic Development Journal (WEDJ), 2021)
This research aims to determine the effect of the Money Supply (JUB), the BI Rate and Inflation on Economic Growth in Indonesia for the Period 2009-2018. The object of this research is the Amount of Money Supply, BI Rate, Inflation and Economic Growth in Indonesia. The data analysis technique used is multiple linear regression. The results showed that the money supply had a positive effect on economic growth with a regression coefficient of 0.804 and a sig value of 0.016 <0.05. This means that the higher the money supply, the higher economic growth. BI Rate has a positive effect on economic growth with a regression coefficient of 0.159 and a sig value of 0.022 <0.05. This means that the higher the BI Rate, the higher economic growth. Inflation has a negative effect on economic growth with a regression coefficient of -0.063 and a sig value of 0.039 <0.05.